Current Concepts in Cranial Reconstruction: Review of Alloplastic Materials. Issue 8 (19th August 2022) - Johnston, Darin T.; Lohmeier, Steven J.; Langdell, Hannah C.; Pyfer, Bryan J.; Komisarow, Jordan; Powers, David B.; Erdmann, Detlev
Abstract : Background: Cranioplasty for acquired cranial defects can be complex and challenging. Benefits include improved cosmesis, protection of intracranial structures, and restoration of neurocognitive function. These defects can be reconstructed with preserved craniectomy bone flaps, split autografts, or alloplastic materials. When alloplastic cranioplasty is planned, the material should be carefully selected. There is confusion on which material should be used in certain scenarios, particularly in composite defects. Methods: The PubMed database was used to conduct a nonsystematic review of literature related to these materials and the following factors: time required in preoperative planning and fabrication, intraoperative time, feasibility of intraoperative modification, fixation method (direct or indirect), implant cost, overall complication rate, and surgical revision rates. Results: Surgical revision rates for alloplastic materials range from 10% to 23%. Retention of titanium mesh at 4 years is 85% in composite reconstruction with free fasciocutaneous and free myocutaneous flaps. In composite reconstruction with locoregional and free muscle flaps, the retention of titanium mesh at 4 years is 47%. The retention of nontitanium and nonpreserved autogenous reconstruction is 72% and 82%, respectively. Conclusions: Alloplastic materials should be considered for reconstruction of large (>100 cm 2 ) cranial defects, especially for adult patients younger than 30 years, and all patients with bone flaps that are fragmented or have been cryopreserved for an extended period. Preformed titanium mesh provides a favorable primary reconstructive option when a staged reconstruction is not possible or indicated but should be avoided in composite defects reconstructed with locoregional scalp and free muscle flaps.